2020
DOI: 10.3389/fmicb.2020.01279
|View full text |Cite
|
Sign up to set email alerts
|

Phospholipase C From Alternaria alternata Is Induced by Physiochemical Cues on the Pear Fruit Surface That Dictate Infection Structure Differentiation and Pathogenicity

Abstract: To investigate the mechanisms of phospholipase C (PLC)-mediated calcium (Ca 2+) signaling in Alternaria alternata, the regulatory roles of PLC were elucidated using neomycin, a specific inhibitor of PLC activity. Three isotypes of PLC designated AaPLC1, AaPLC2, and AaPLC3 were identified in A. alternata through genome sequencing. qRT-PCR analysis showed that fruit wax extracts significantly upregulated the expression of all three PLC genes in vitro. Pharmacological experiments showed that neomycin treatment le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 68 publications
(87 reference statements)
0
13
0
Order By: Relevance
“…The PH domain is localized at the N-terminus of PLCs and is responsible for membrane PtdIns(4,5)P 2 binding [ 67 ]. PLCs, such as those from PLC1 from Alternaria alternata [ 68 ] and Magnaporthe oryzae [ 69 ], encode a PH domain, which is in tandem with the EF-hand Ca 2+ -binding, the catalytic X and Y, and the phospholipid-binding C2 domains. Regulation of phospholipid-binding of PLC is mediated by association of PtdIns4P 5-kinase and Ca 2+ to the PH and C2 domains, respectively [ 70 ].…”
Section: Resultsmentioning
confidence: 99%
“…The PH domain is localized at the N-terminus of PLCs and is responsible for membrane PtdIns(4,5)P 2 binding [ 67 ]. PLCs, such as those from PLC1 from Alternaria alternata [ 68 ] and Magnaporthe oryzae [ 69 ], encode a PH domain, which is in tandem with the EF-hand Ca 2+ -binding, the catalytic X and Y, and the phospholipid-binding C2 domains. Regulation of phospholipid-binding of PLC is mediated by association of PtdIns4P 5-kinase and Ca 2+ to the PH and C2 domains, respectively [ 70 ].…”
Section: Resultsmentioning
confidence: 99%
“…In order to precisely regulate intracellular calcium signals, organisms have also evolved several calcium-sensing proteins to respond to different ranges of Ca 2+ concentration levels [ 70 ]. CaM, located downstream of phospholipase C [ 71 ] in the calcium signaling pathway, is a very important Ca 2+ sensor that can sense the change of intracellular Ca 2+ concentration and regulate a series of downstream target proteins by binding with Ca 2+ [ 72 , 73 , 74 ]. CaN, as a Ca 2+ and CaM dependent serine/threonine protein phosphatase, is composed of the catalytic subunit CNA and the regulatory subunit CNB [ 75 , 76 , 77 , 78 , 79 ], and is the central mediator of the Ca 2+ /calmodulin/calcineurin/Crz1 signaling pathway.…”
Section: Calcium Signaling Pathway In Fungal Cellmentioning
confidence: 99%
“…PDA media were added with TFP at the final concentrations of 10 μmol l −1 , inoculated with mycelium of A.alternata and cultured in an incubator at 28°C for 5 days, and ~0.25/0.5 g of the mycelium was sampled for melanin and toxin extracting, respectively. The extraction and determination of melanin and toxins were performed according to the method of Wang et al (2016) and Huang et al (2020). All the experiments were repeated at least three times.…”
Section: Melanin and Toxins Assaysmentioning
confidence: 99%
“…Although numerous studies have shown that CaM is involved in the regulation of fungal growth, secondary metabolism and pathogenicity, its regulatory role is diverse and complex depending on the pathogen. Our recent studies showed that protein kinase A (PKA) in the cAMP/ PKA pathway (Zhang et al, 2020), Sho1 in MAPK cascades (Liu et al, 2021) and PLC (Huang et al, 2020) in the Ca 2+ signalling pathway were involved in the vegetative growth, stress response and infection structure differentiation of A. alternata in response to hydrophobic and pear wax. At the same time, the importance of the Ca 2+ signalling pathway for infection structure differentiation of A. alternata was evaluated through the specific inhibitors of the Ca 2+ signalling pathway.…”
Section: Introductionmentioning
confidence: 99%